Identification and evaluation of drug-related problems in community pharmacy in Turkey: a descriptive prevalence study - Muhammed Yunus Bektay; Yunus Emre Ayhan; Merve Çakmak; Berre Mercumek (BMC Primary Care)
Abstract Background Community pharmacies (CPs) are key healthcare providers, playing a significant role in optimizing drug therapy and preventing drug-related problems (DRPs). This study aims to assess the prevalence, characteristics, and related factors of DRPs in Turkish patients in the community pharmacy setting. Methods A cross-sectional, prospective study was conducted between December 2023 and December 2024 in a community pharmacy. A total of 100 patients were included after excluding those with incomplete data. DRPs were evaluated using the PCNE V9.1 classification system, while Medication Adherence Report Scale (MARS) and Medication Regimen Complexity Index (MRCI) were used to assess adherence and regimen complexity. Results A total of 162 DRPs were identified, with an average of 1.6 DRPs per patient. DRPs were significantly associated with factors such as higher body mass index (p = 0.005), polypharmacy (p < 0.001), use of antidiabetic (p < 0.001) and antihypertensive medications (p = 0.005), and a higher number of comorbidities (p = 0.005). No significant relationship was observed between medication adherence and DRPs (p > 0.05). Discussion This study is among the first in Türkiye to evaluate DRPs in chronic disease management within a community pharmacy setting. The findings highlight the importance of clinical pharmacists in identifying and managing DRPs and suggest the need for integrated interventions in healthcare teams to improve patient outcomes and medication safety.